Effects of Endotoxin on Gluconeogenesis, Glycogen Synthesis, and Liver Glycogen Synthase in Mice - McCallum, R. E. (1973)
This study was undertaken to characterize the nature of carbohydrate loss due to endotoxin poisoning in mice and to elucidate mechanisms responsible for the changes. Female ICR mice, fasted overnight, were injected intraperitoneally with a mean lethal dose of endotoxin extracted from Salmonella typhimurium strain SR-11. Liver glycogen levels, alanine-U-(14)C and pyruvate-2-(14)C incorporation into blood glucose and liver glycogen, glucose-U-(14)C incorporation into liver glycogen, and liver glycogen synthase activities were measured at intervals after treatment. Liver glycogen in fasted mice given endotoxin was diminished significantly as early as 1 h after treatment. Liver glycogen synthase was significantly decreased in poisoned mice at 17 h. The use of actinomycin D showed that the induction of this enzyme due to fasting or hydrocortisone, or both, was inhibited by endotoxin. The incorporation of the (14)C-label from alanine-U-(14)C, pyruvate-2-(14)C, or glucose-U-(14)C into blood glucose and liver glycogen was substantially impaired in endotoxemic animals at 12 h. Decreases in incorporation occurred as early as 4 h after treatment. The progressive increase in glycogen synthase activity observed in fasted controls was not seen in endotoxin-poisoned mice. The administration of a glucose or pyruvate load to endotoxin-treated mice did not restore gluconeogenesis, glycogen synthesis, or liver glycogen synthase activity to normal levels. The in vivo activation of glycogen synthase by glucose was significantly reduced in endotoxemic animals. These changes indicate reduced carbohydrate synthesis as a probable cause for rapid sugar loss during endotoxemia in mice.